Studying the status of some ornamental plant nursery's in the Syrian coastal region - Nassour, Mazen (Latakia University Journal -Biological Sciences Series, 2013)
Ornamental plants considered one of the modern plantation, which should be introduced in the future agricultural development plan confirmed by field studies for the most important ornamental seed plants as a samples for data collections. Through information and field data it can be concluded that, most of nursery's of ornamental plants were in a small size (less than 2.5 hectare) in comparison with some other propagated plants due to the absence of specialization. We observed a shortage in a propagated plant materials especially cut-flowers which considered the most important product. This research observed also many problems facing the producers leading to high production cost: preliminary materials, agriculture and propagation materials, expert workers beside obstacles in exporting and absence in observation and governmental help.